Characterization and biodegradation of poly (vinyl alcohol)/cassava starch [electronic resource] - Nor Sarizal Nor Hassan, 1987- (2013)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2013